Successful Vaginal Delivery after Induction of Labour in a Patient Treated for Non-Hodgkin’s Lymphoma of the Cervix: A Case Report and Literature Review - Paola Quaresima; Gabriele Saccone; Valeria Zuccalà; Giuseppe Guarascio; Livio Leo; Giuseppina Amendola; Fulvio Zullo; Michele Morelli; Roberta Venturella (Case Reports in Obstetrics and Gynecology)
Objective. Primary non-Hodgkin’s lymphomas of the cervix are rare; they represent about 1% of all cases. There are no available guidelines regarding the safest mode of delivery after treatment and resolution of a cervical lymphoma. Case Report. We report the first case of a successful vaginal delivery after induction of labour in a woman recovered from a primary large B-cell lymphoma of the cervix and a literature review. Conclusion. In carefully selected patients with fully treated non-Hodgkin’s lymphoma of the cervix with no residual disease, induction of labour via prostaglandins pessary may be a safe option if indicated.